2019
DOI: 10.1002/anie.201904469
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Vacancy Diffusion and Condensation in Lithium‐Ion Battery Cathode Materials

Abstract: Oxygen vacancies (OV) are native defects in transition metal (TM) oxides and their presence has a critical effect on the physicochemical properties of the oxide. Metal oxides are commonly used in lithium‐ion battery (LIB) cathodes and there is still a lack of understanding of the role of OVs in LIB research field. Here, we report on the behavior of OVs in a single‐crystal LIB cathode during the non‐equilibrium states of charge and discharge. We found that microcrack evolution in a single crystal occurs due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
72
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(74 citation statements)
references
References 41 publications
1
72
0
1
Order By: Relevance
“…[3,34,35] As we all know, surface coating is a popular and effective strategy to alleviate the side reactions between cathode and electrolyte. [3,[36][37][38][39] Namely, the electrochemical performance of this single-crystal Ni-rich cathode may have a room for further improvement, if the surface modification is conducted.…”
Section: Resultsmentioning
confidence: 99%
“…[3,34,35] As we all know, surface coating is a popular and effective strategy to alleviate the side reactions between cathode and electrolyte. [3,[36][37][38][39] Namely, the electrochemical performance of this single-crystal Ni-rich cathode may have a room for further improvement, if the surface modification is conducted.…”
Section: Resultsmentioning
confidence: 99%
“…Lee et al suggested that the directional cracking through the TEM and STEM, the migration of oxygen vacancy in the bulk has a preference of facet. [25] The STEM results from Yan et al also support that the spinel phase and oxygen loss behavior in the bulk. [23] Furthermore, the enhanced ABF (eABF) imaging by 4D STEM reported by Ahmed et al sheds light on the better observation of light elements such as oxygen.…”
Section: Spectroscopic Techniques To Probe the Oxygen Redox Related Phenomenonmentioning
confidence: 86%
“…Figure25. Concentration gradient in coating: a) Representation of nickel-rich core for high capacity covered by a manganese-rich shell; the shell comprises crystallites with a columnar or slab-like morphology, with lithium diffusion direction radiating from particle center as indicated by the blue arrows; b) transmission electron microscopy (TEM) images of the columnar/slab-like crystallites comprising the manganese-rich shell; Reproduced with permission.…”
mentioning
confidence: 99%
“…Previous research on oxygen vacancies focused on catalysis [22][23][24][25][26]. Only a few studies analyzed the effect of oxygen vacancies on lithium storage [27]. These limited studies suggest that the introduction of oxygen vacancies can improve electrical conductivity and increase active site, which is beneficial to enhancing lithium storage remarkably [28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%